Kształcenie nauczycieli (dwie wersje) = Teacher training (two versions) - Hajduk, Edward (1932-2015) (Zielona Góra: Uniwersytet Zielonogórski)
Two concepts of education may be distinguished at the university level. One concept assumes that the student should acquire the language and knowledge of a certain realm of symbolic culture or a given realm of science. They will use the theoretical knowledge themselves to create programs of practical actions or to implement such a program. Acquisition of theoretical knowledge is dispensable for introducing changes in practical actions (treatment, teaching, material goods production). Theory changes practice.
Keywords: nauczyciele; edukacja